Effectiveness of the Family and Friends CPR course in learning cardiopulmonary resuscitation in relatives of patients with high cardiovascular risk or who have suffered a cardiovascular event - Bruno Enzo Vargas-Sánchez; Miluska Madeleine Salazar-Arteaga; Aida Del Carmen Rotta-Rotta; Roy Germán Dueñas-Carbajal (Iberoamerican Journal of Medicine, 2021)
Introduction: Early, high-quality cardiopulmonary resuscitation (CPR) increases survival rates in cardiac arrest. Although most cases occur at home and are witnessed, CPR is performed in few of these cases. For this reason, teaching CPR is especially important in relatives of patients with high cardiovascular risk. Therefore, the aim of this study was to demonstrate the effectiveness of the Family and Friends CPR course in the theoretical and practical learning of cardiopulmonary resuscitation in relatives of patients with high cardiovascular risk or who have suffered a cardiovascular event. Materials and methods: We carried out an analytical, quasi-experimental, prospective, before-and-after study. We selected 20 participants during outpatient consultation at the Cardiology Department of the Cayetano Heredia Hospital in Lima, Peru. A theoretical knowledge questionnaire and an adult CPR checklist were used to assess the level of theoretical and practical knowledge, respectively. The theoretical knowledge was measured at three points in time (before, immediately after and one month after the intervention) and the practical skills at two points in time (immediately after and a month after the intervention). Results: The level of theoretical knowledge was low (8.64 ± 2.47) before the intervention, achieving a good level of knowledge immediately after (17.33 ± 2.02) and one month later (16.5 ± 1.91). Furthermore, the medians of the level of practical knowledge were 15 immediately after and one month later, showing that they maintained a good level of practical knowledge. Conclusions: The Family and Friends CPR course was effective in the theoretical and practical learning of CPR in the studied population, and was sustained one month after the intervention.